1997
DOI: 10.1007/s002180050407
|View full text |Cite
|
Sign up to set email alerts
|

A (p/E) calculation of strong pionic decays of baryons

Abstract: Strong pionic decays of baryons are studied in a non-relativistic quark model framework via a convergent (p/E) expansion of the transition operator. Results are compared to the ones obtained within a more conventional (p/m) expansion.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
9
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 10 publications
4
9
0
Order By: Relevance
“…∆m 15,bol values range from 0.20 to 1.37 mag, with SNe Ic making up the extremes of this distribution. The possibility of a Phillips-type relation for GRB-SNe, suggested by Schulze et al (2014) and independently confirmed by Cano (2014); Li & Hjorth (2014), is evident here for the bolometric light curves of the majority of the SNe Ic-BL sample.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…∆m 15,bol values range from 0.20 to 1.37 mag, with SNe Ic making up the extremes of this distribution. The possibility of a Phillips-type relation for GRB-SNe, suggested by Schulze et al (2014) and independently confirmed by Cano (2014); Li & Hjorth (2014), is evident here for the bolometric light curves of the majority of the SNe Ic-BL sample.…”
Section: Discussionsupporting
confidence: 74%
“…(1) Utrobin (1994); (2) Sahu et al 2009;2009bb, Pignata et al 2011, although strong radio emission suggests the presence of relativistic material in this SN, Soderberg et al 2010). The standardising of GRB-SN light curves has been further studied by Cano (2014); Li & Hjorth (2014), who indeed find relations based on light curve properties to allow their cosmological use, confirming the indications from the relatively cruder analyses in Schulze et al (2014) and here.…”
Section: Bolometric Light Curvesmentioning
confidence: 99%
“…This value compares well to the value that can be obtained from meson decays 6 but is significantly smaller than the one derived from baryon decays 4,8 . Within conventions, the sign that is required in some cases is also known.…”
Section: Baryon: Submitted To World Scientific On November 15 2017supporting
confidence: 80%
“…Such ratios are expected to be quite sensitive to the details in the potential, and in the decay operator [147]. [166]. The first column identifies the particular decay.…”
Section: Kimentioning
confidence: 99%